RAGAM HIAS SENI UKIR PADA BANGUNAN TRADISIONAL BANJAR DULU DAN SEKARANG - Sunarningsih Sunarningsih (Balai Arkeologi Kalimantan Selatan, 2008)
Banjarese traditional house-on-stils present different characteristics to those of other communities. In the past, such houses were abundantly built, but one can hardly ever build one today. Presently, many old Banjarese traditional house-on-stils have highly weathered and damaged. Such house which is richly ornamented is the bubungan tinggi. This article discusses ornaments carved on the old Banjarese traditional house-on-stilts, and the possibilities of people today persist on using it.